Upplevelsefokuserad Utställningsproduktion : Hur utställningsproduktion och upplevelseproduktion kan kombineras för att skapa utställningar som attraherar Generation Y - Fält, Astrid; Martin, Sofia (2012)
Whilst society is moving towards an “experience” society, new demands are placed on organisations, but also on museums. We have identified that Generation Y (born in the 80´s and 90´s) are less likely to visit museums than older generations. This could be viewed as worrying since Generation Y are the visitors of tomorrow and consumers of culture. Generation Y is the first generation to grow up completely surrounded by technology. They place high demands on their surroundings and want to be entertained, which is a need museums must meet.The purpose of this paper is to examine whether or not theories from experience production can be applied to exhibition productions in order to create attractive exhibitions for Generation Y. This was done via a conceptual development of the permanent exhibition at the museum of Piteå.We discovered that experience production and exhibition production advantageously can be combined. We have named this combination Experience-focused exhibition production. We believe that Experience-focused exhibition production could be the key to reaching Generation Y since it is made up of the components that the generation want and appreciate.For the conceptual development we focused on using simple means, small resources and good target group knowledge to develop the permanent exhibition at the museum of Piteå to become an Experience-focused exhibition production. Through an interplay of text, picture, sound, film, objects and other sensory impressions the exhibition at the museum of Piteå can be developed to attract Generation Y. The parts that make up our conceptual development can, with great probability, also be applied to other museums and exhibitions, albeit with some modifications. Validerat; 20120627 (anonymous)